THE SOCIAL SECURITY REFORM AND THE IMPACTS ON THE RETIREMENT OF PUBLIC SERVANTS: BETWEEN THE TRANSITION RULES AND THE WORSENING QUALITY OF LIFE - Morais, Alekson Junior Gomes; Penha Junior, José; e Silva, Ana Carolinna Barros; Santos, Jane Karla de Oliveira; de Oliveira, Luiz Carlos Carvalho (Seven Editora, 2025)
This study examines the impact of the 2019 Social Security Reform on the retirement conditions of public servants linked to the General Social Security Regime (RGPS), in contrast to those who have their own Social Security Regime (RPPS). With the reform, there were important changes in age requirements, contributions, and the calculation of benefits, which raises the central question: "What is the impact of these changes on the quality of life and financial security of public servants?" The research is based on three main hypotheses: the first suggests that stricter requirements have reduced access to retirement, compromising quality of life; the second points to a decrease in the value of benefits, caused by the new calculation formula; and the third indicates that, in order to meet the established criteria, civil servants can postpone retirement, jeopardizing their financial security and well-being. The study confirmed that the new rules imposed additional challenges to pension planning and encouraged prolonged permanence in the labor market, which impacts the quality of life of civil servants in the pre-retirement phase. In addition, it was found that the new calculation methodology resulted in significant reductions in the amounts of benefits, generating uncertainties and affecting the dignity and financial balance of retirees. This investigation is relevant, as the reform directly affects millions of public servants without RPPS, being a central point to understand the current social security scenario and support governmental and personal decisions regarding social security planning, with a view to ensuring future security and quality of life. DOI: https://doi.org/10.56238/sevened2025.018-003